A stimulus rate that is not influenced by homosynaptic post-activation depression in chronic stroke. (1st October 2020) - Yurttutmuş, Zeynep; Ekici Zincirci, Dilara; Bardak, Ayse Nur; Topkara, Betilay; Aydın, Tugba; Karacan, Ilhan; Türker, Kemal S
Abstract: Purpose: To determine a stimulus rate that is not influenced by homosynaptic post-activation depression for H-reflex studies in patients with chronic spasticity. Materials and methods: A cohort of 15 chronic stroke patients with soleus spasticity who received inpatient treatment at our rehabilitation centre participated in this study. The effect of stimulus frequency related depression on H-reflex size was tested using four different stimulus rates (0.1, 0.2, 0.3 and 1 Hz). The affected sides stibial nerve was stimulated by a bipolar electrode. The H-reflex was recorded from the affected sideed sidee sidehe affected smine stimulus frequency related depression of H-reflex size, amplitude of the first H-reflex response (H1 ) was used as control and amplitude of the second H-reflex response (H2 ) as test. Results: H2 amplitude for frequency of 1 Hz, 0.3 Hz, 0.2 Hz and 0.1 Hz were 74.3, 84.1, 85.5 and 92.7% of H1, respectively. Depression of H2 amplitude was statistically significant for 1 Hz, 0.3 Hz and 0.2 Hz ( p < 0.001, p = 0.002, p = 0.024, respectively). Conclusions: Higher frequency stimulation of Ia afferents than 0.1 Hz induced a stimulus frequency-related depression of H-reflex size in patients with chronic spasticity. The optimal stimulus rate for H-reflex was found to be 0.1 Hz.